Compliance with the principle of equality of arms with regard to the expertise and findings made during the prosecution - Gradinaru, Sandra (Acta Universitatis Danubius. Juridica, 2023)
The paper addresses from a jurisprudential perspective the respect of the principle of equality of arms in the situation of administration, during the criminal investigation, of a specialized finding by a specialist working in the interests of the Public Ministry and the defendant disputes the conclusions of such a report. There are many situations in the judicial practice in which the defence challenges such reports even from the course of the criminal investigation and subsequently before the court of law, however, the judicial bodies do not administer technical expertise by independent experts to confirm or repel the findings of such a report. We appreciate that the criminal procedural law does not ensure the observance of the right to a fair trial of the defendant. Its possibility to challenge the contents of the specialized report is left during the criminal investigation at the discretion of the prosecutor, the defense being placed in an unfair situation. On the one hand, the subjectivism of the judicial body is noted in the assessment of the need to administer an expertise to confirm the issues contested by the defendant. Equally, by ordering the performance of a specialist finding, the defendant is deprived of the opportunity to formulate objectives or to benefit from the participation of a party expert. We believe that the exercise of the defendant's rights of defence during the criminal investigation cannot depend in a decisive way on the assessment of the case prosecutor. This paper includes proposals de lege ferenda to restore the balance between the prosecution and defense and ensure a fair trial for the defendant. The paper is addressed to professionals (judges, prosecutors, lawyers), as well as to theoreticians and litigants.